Preliminary Investigation On Gas Separation Ability Of Polysulfone/Pebax 1657 Composite Membrane - Sunarti, Abd Rahman; M. S., Abdul Wahab; Nurul Farhana, D. (Penerbit Universiti Teknologi Malaysia, 2016)
Human activities related to coal, petroleum, natural gases and few other energy sources emit carbon dioxide (CO2) gas to environment and increase global warming. The emission of CO2 gas from human activities cannot be avoided as they are the main sources of energy. The separation and purification of these gases before they are freely escaped to the atmosphere could be a turning point for a better future. Membranes are one of the methods widely used for gas separation as they are simple mechanism and costly cheap. In this study, Polysulfone (PSf) was introduced as composite membranes with Polyether block amide (Pebax 1657) as a dense selective layer for CO2/N2 separation. For the dope preparation, 18% of PSf with 2% Polyethylene glycol (PEG) as an additive was diluted in 80% N-methyl-2-pyrrolidone (NMP) meanwhile, the Pebax 1657 coating solution has been prepared by using 4% Pebax 1657 with 6% lithium chloride (LiCl) as an additive in 70/30 water/ethanol solution. Cross sectional view of the film showed a wide and long cavity with finger-like structure from 6 µm to 10 µm wide with Pebax 1657 selective layer thickness of 29.3 µm. FTIR analysis has proved that all elements present in the film belong to the Pebax 1657, PSf, PEG and LiCl. The permeance test shows a very slight improvement of uncoated and coated samples where uncoated PSf selectivity was found to be 1.17 while the coated sample was 1.23. Even though the permeance result quite low and almost no separation occurs but the slight improvement of uncoated and coated PSf is noticeable and have the potential for future improvement.